High Density DNA Data Storage Library via Dehydration with Digital Microﬂuidic Retrieval - Newman, Sharon; Stephenson, Ashley; Willsey, Max; Nguyen, Bichlien; Takahashi, Christopher N.; Strauss, Karin; Ceze, Luis (Nature Communications, 2019)
DNA promises to be a high density data storage medium, but physical storage poses a challenge. To store large amounts of data, pools must be physically isolated so they can share the same addressing scheme. We propose the storage of dehydrated DNA spots on glass as an approach for scalable DNA data storage. The dried spots can then be retrieved by a water droplet using a digital microﬂuidic device. Here we show that this storage schema works with varying spot organization, spotted masses of DNA, and droplet retrieval dwell times. In all cases, the majority of the DNA was retrieved and successfully sequenced. We demonstrate that the spots can be densely arranged on a microﬂuidic device without signiﬁcant contamination of the retrieval. We also demonstrate that 1 TB of data could be stored in a single spot of DNA and successfully retrieved using this method.
(2019)10:1706